Minimum ignition energy of medicinal powder – Florfenicol and Tilmicosin. (January 2016) - Zhang, Xiaoliang; Shen, Qian; Shen, Xiaobo; Zhang, Zhikai; Xu, Sunjie; Ye, Shengjun
Abstract: This work aims to help improve the electrostatic safety design and explosion prevention of medical facilities. In this study, the minimum ignition energies (MIEs) of Florfenicol, Tilmicosin and mixtures of Florfenicol and Tilmicosin at ratios of 1:1, 1:2, 2:1 and 1:4 were measured in a Hartmann apparatus. The results demonstrated that the MIEs for Florfenicol, Tilmicosin and mixtures of Florfenicol and Tilmicosin at ratios of 1:1, 1:2, 2:1 and 1:4 are 200, 70, 180, 150, 200 and 110 mJ, respectively. Tilmicosin is more sensitive to static electricity, which is more dangerous than the other two powders examined in this paper. Furthermore, the MIEs of the mixtures are proportional to the Florfenicol content. For all powders, the MIE first decreased with the powder mass and later reached its minimum value. In addition, scanning electron microscopy (SEM), differential scanning calorimetry (DSC) were used to investigate the morphological specificity and thermal decomposition of the powders to elucidate the parameters governing the powder explosions further. Highlights: We measured the MIE of medicinal powders (Florfenicol and Tilmicosin) and their mixtures. The data showed non linear effect of explosion severity with the dust concentration. The MIE of the mixtures is proportional to the Florfenicol content.